Grounding Criterion: Toward a Formal Theory of Grounding - Horvitz, Eric; Paek, Tim (2000)
In a conversation, participants establish and maintain their mutual belief that their utterances have been understood well enough for current purposes – a process that has been referred to as grounding. In order to make a contribution to the conversation, participants typically do more than just produce the right utterance at the right time; they coordinate the presentation and acceptance of their utterances until they have reached a sufficient level of mutual understanding to move on, a level defined by the grounding criterion . Recent interest in employing grounding for use in collaborative dialog systems has highlighted difficulties in rendering hitherto qualitative intuitions about grounding into formal terms. In this paper, we propose a formalization of grounding based on decision theory that captures key intuitions about the contribution model while providing an explicit method for determining the grounding criterion. We illustrate the formalization by reviewing interactions between a user and a prototype spoken dialog system called the Bayesian Receptionist .